2016
DOI: 10.1038/srep32184
|View full text |Cite
|
Sign up to set email alerts
|

3D-engineering of Cellularized Conduits for Peripheral Nerve Regeneration

Abstract: Tissue engineered conduits have great promise for bridging peripheral nerve defects by providing physical guiding and biological cues. A flexible method for integrating support cells into a conduit with desired architectures is wanted. Here, a 3D-printing technology is adopted to prepare a bio-conduit with designer structures for peripheral nerve regeneration. This bio-conduit is consisted of a cryopolymerized gelatin methacryloyl (cryoGelMA) gel cellularized with adipose-derived stem cells (ASCs). By modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
104
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 52 publications
0
104
0
Order By: Relevance
“…Co-culture can be comprised of heterogeneous cells to cells; cells with specific GFs or other pharmacologic agents; and cells to drive the behavior of other cells. [19],[20],[50],[51],[68]–[73] Any use of these cells as models are possible if some type of suitable platform is available that will enable them to attach and perform their function. Therefore, 3D cell culture success depends on the matrix to be seeded, such as the polymeric scaffolds that offer the 3D structures.…”
Section: Selection Of Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Co-culture can be comprised of heterogeneous cells to cells; cells with specific GFs or other pharmacologic agents; and cells to drive the behavior of other cells. [19],[20],[50],[51],[68]–[73] Any use of these cells as models are possible if some type of suitable platform is available that will enable them to attach and perform their function. Therefore, 3D cell culture success depends on the matrix to be seeded, such as the polymeric scaffolds that offer the 3D structures.…”
Section: Selection Of Cellsmentioning
confidence: 99%
“…[73] The choice of material is crucial on 3D printing technology specially on inkjet bioprinting, since it needs to be printed liquid and then form a solid 3D structure. 3D structure is achieved by the use of materials that can be cross-linked after the deposition by chemical, pH or ultraviolet mechanisms.…”
Section: D Cell Culture Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some drawbacks such as misalignment of nerve bundles, curling of nerve ends, or the proliferation of connective tissue at anastomotic sites still complicate treatments (Nakayama et al, 2007). Noteworthy, Gou and collaborators (Hu et al, 2016) described the use of GelMA and ADSCs to facilitate rat sciatic nerve repair. Gelatin can be cross-linked with genipin (Chen et al, 2005) and EDC-NHS (Chang et al, 2007) or under the form of GelMA-LAP (Xia et al, 2018;Zhou, Lee, & Tan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, results between the composite conduit group and the autograft group were of no statistical differences.All results above showed that the composite conduit filled with EHS Hydrogel can promote the repair of peripheral nerve and may become a promising way to treat peripheral nerve defects.3D bioprint, chemical cross-link, ECM, GelMA, nerve repair Conduits were produced as described earlier (Hu et al, 2016). To date, commercially available artificial nerve conduits comprise hollow tubes.…”
mentioning
confidence: 99%